Effect of Fermentation Time on the Production of Ambon Banana Weevil Waste Bioethanol - Budiastuti, Herawati -; Zulfa, Salma Indana; Sihombing, Nova; haryadi, haryadi; Muhari, Emma Hermawati; Soeswanto, Bambang; Widiastuti, Endang; Pullammanappallil, Pratap (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
The increase in population in Indonesia is directly proportional to the increase in the use of vehicles which results in an increase in fuel demand. The amount of fossil fuels continues to decrease and cannot be renewed, so alternative energy is needed, one of which is bioethanol. This study aims to make bioethanol from banana weevil waste, to determine the effect of fermentation time on the concentration of banana weevil bioethanol and to determine the concentration of bioethanol after going through the purification stage. The production of banana weevil bioethanol begins with the process of cutting the banana weevil which is then mashed with the help of water and then squeezed and starch is obtained and then hydrolyzed with the addition of glucoamylase and alpha-amylase enzymes for further anaerobic fermentation with the help of Saccharomyces cerevisiae with a concentration of 25%. In this study, variations of fermentation time were carried out for 5, 7, 9, and 10 days. The best fermentation time was obtained from 9 days of fermentation, where the conversion of glucose to bioethanol was 51%. The results of the analysis using a refractometer showed that the concentration of bioethanol obtained was 16.20% (v) which was obtained from fermentation for 9 days and purification using a rotary evaporator at a pressure of 360 mbar and a temperature of 500C.